ANTIOXIDANT AND CHEMOTHERAPEUTIC POTENTIAL OF CURCUMA AMADA RHIZOME EXTRACT ON BENZO(A)PYRENE INDUCED CERVICAL CARCINOMA IN SPRAGUE DAWLEY RATS - PALANISAMY, VASUNDRA DEVI; Samiappan, Suja (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To evaluate the antioxidant and chemotherapeutic potential of Curcuma amada Rhizome extract on benzo(a)pyrene (BaP) induced cervical carcinoma in Sprague Dawley rats. Methods: A total of 30 female Sprague Dawley rats were selected to establish cervical cancer model and then divided into 5 groups at random with six mice in each group. Group 1 control, Group 2 BaP (oral), Group 3 BaP for 8 weeks and post-treated with cisplatin (intravenous administration), Group 4 BaP for 8 weeks and post-treated with 250 mg of ethanol extract of C. amada (oral), Group 5 BaP for 8 weeks and post-treated with 500 mg of ethanol extract of C. amada (oral). 4 weeks after the treatment, the animals were sacrificed, serum separated, and cervical tissues were dissected. Antioxidants and the markers carcinoembryonic antigen (CEA), cancer antigens (CAs) 125, gamma glutamyltransferase (GTT) were assayed in serum and the tissue was used for analyzing tumor burden and sectioned for histopathological assays.10% tissue homogenate was estimated for antioxidants and membrane-bound enzymes. Results: BaP treated group showed significant (p<0.001) incidence of tumor burden, decreased activities of antioxidants, elevated lipid peroxidation, Na+/K+ adenosine triphosphatase (Na+K+ATPase), Calcium adenosine triphosphatase (Ca2+ATPase), Magnesium adenosine triphosphatase (Mg2+ ATPase), CEA, CA 125, GTT. Treatment with C. amada rhizome extract and standard drug cisplatin reverted the antioxidants, serum markers and tissue enzymes. Conclusion: From the results, it can be concluded that C. amada Rhizome extract ameliorated BaP induced oxidative stress in the cervical carcinogenicity of rats. Keywords: Curcuma amada, In vivo antioxidant, Chemotherapy, Benzo(a)pyrene, Cervical carcinoma, Tumor markers.